Inactivated vaccine injection and immunoglobulin G levels related to severe coronavirus disease 2019 (Delta) pneumonia in Xi’an, China: A single-centered, retrospective, observational study - Yang, Han; Ma, Jinbao; Li, Aifang; Lei, Jing; Shang, Fenqing; Cheng, Yue; Han, Bei; Li, Hongbo; Chen, Yuee; Yang, Yuanli; Xu, You (Frontiers in Cellular and Infection Microbiology, 2022)
The World Health Organization declared a public health emergency of international concern in January 2020. The Delta variant became the main epidemic strain on 11 May 2021. Vaccines were proven highly effective in controlling hospitalization and deaths associated with severe acute respiratory syndrome coronavirus 2 infections. Real data on vaccine efficacy against B.1.617.2 infection in the Chinese population were currently limited. This study aimed to evaluate the protective effect of inactivated vaccine injection and immunoglobulin (Ig) G levels in coronavirus disease 2019 (COVID-19) severity. This retrospective study included patients with COVID-19 in Xi’an Chest Hospital from December 2021 to January 2022. The protective effect of inactivated vaccine injection and IgG levels on COVID-19 severity was analyzed using multiple logistic regressions. A total of 580 patients were included in the study, of whom 158 (27.24%) were mild, 412 (71.03%) were moderate, 5 (0.9%) were severe, and 5 (0.86%) were critical. Severe case (including severe and critical) rates were 1.72% (10/580). Compared with the unvaccinated group, the vac+IgG− group had a 0.21 (0.02–2.05)-fold risk of suffering from severe cases, and the vac+IgG+ group had a 0.05 (0–0.63)-fold risk of suffering from severe cases. Of the 10 severe cases, 8 were older than 60 years, 8 were men, 8 had underlying diseases, 6 were in the unvaccinated group, and 2 were in the vac+IgG− group. Vaccination and sufficient IgG antibody production can protect patients with COVID-19 from severe cases. Booster vaccine injection can produce a stronger immune response and protection.